An optimised publish/subscribe middleware for peer-to-peer systems. (11th September 2008) - Garcia-Sanchez, Antonio Javier; Garcia-Sanchez, Felipe; Pavon-Marino, Pablo; Garcia-Haro, Joan
The publish/subscribe paradigm provides a very effective and reliable scheme to implement Peer-To-Peer (P2P) networks. In these systems, the reduction of the number of messages associated to the searching procedure is a crucial issue. In this paper, we study the current publish/subscribe systems and propose an Optimised Middleware (OMCPS), suitable for the implementation of large-scale content delivery systems. The main idea behind our proposal is to reduce the conventional message distribution and searching process by using a well-known decentralised algorithm (the Chord). In addition, the internal OMCPS organisation among the Servers that conforms the P2P system is transparent to the consumer and supplier applications.